Employment, unemployment, and underemployment in Africa - Stephen Golub; Faraz Hayat (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper documents and analyses the predominance of informal employment in Africa and shows that lack of demand for labour rather than worker characteristics is the main reason for pervasive underemployment. Integration into the global economy and exports of labour-intensive products are vital to boosting the demand for labour in Africa. Africa has some potential to become competitive in light manufacturing, but the most promising avenue for export-led growth of employment in many African countries is agriculture, including traditional cash crops such as cotton, coffee, cocoa, and groundnuts. Contrary to common perceptions, traditional cash crops, which are the source of livelihood for millions of Africans, have many of the features of manufacturing exports: high labour-intensity; potential for quality improvements through technological transfer; and quality-sensitive markets in developed countries. Improvements in the business climate are the key to boosting investment and technology transfer in labour-intensive tradable industries, and thus raising labour demand and employment.
Keywords: J2; J3; Q1; O4; 330; employment; unemployment; underemployment; Africa; labour market; wages